2020
DOI: 10.11646/phytotaxa.428.1.6
|View full text |Cite
|
Sign up to set email alerts
|

<p><strong><em>Navicula gogorevii—</em></strong><strong>a new, large-celled diatom species from Vietnam (Southeast Asia)</strong></p>

Abstract: We describe a new member from the genus Navicula Bory sensu stricto using light and scanning electron microscopy. The new species was found in Vietnam, and is a large-celled species with longitudinal grooves present on the valve exterior. Taxa sharing this feature are known from the genus Navicula, as well as the genera Haslea Simonsen, Craticula Grunow, Gyrosigma Hassall and Proschkinia Karajeva. The new species from Vietnam is compared with other, similar taxa of Navicula, and comments are presented about th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…This feature is similar to another naviculoid genus, Haslea Simonsen, which is morphologically similar to the genus Navicula but is differentiated from Navicula tripunctata. The same structure of pore was observed by us in the very unusual species, Navicula gogorevii Chudaev, Glushchenko, Kulikovskiy, and Kociolek from Vietnam [37]. Another important feature that distinguishes the genus Gandhia from the genus Navicula is the internal structure of the interstriae (virgae).…”
Section: Sem Internal View (Figuressupporting
confidence: 79%
See 2 more Smart Citations
“…This feature is similar to another naviculoid genus, Haslea Simonsen, which is morphologically similar to the genus Navicula but is differentiated from Navicula tripunctata. The same structure of pore was observed by us in the very unusual species, Navicula gogorevii Chudaev, Glushchenko, Kulikovskiy, and Kociolek from Vietnam [37]. Another important feature that distinguishes the genus Gandhia from the genus Navicula is the internal structure of the interstriae (virgae).…”
Section: Sem Internal View (Figuressupporting
confidence: 79%
“…Our investigation of the morphology of Pinnularia and Caloneis has shown that the silica lamina that covers alveoli is an important feature for the delimitation of different groups between these genera [34][35][36][37]. Our comprehensive investigation of Pinnularia and Caloneis, utilizing both molecular and morphological data, substantiates the notion that the presence or absence of silica laminae represents a significant distinguishing feature between independent groups within these genera.…”
Section: Sem Internal View (Figuressupporting
confidence: 73%
See 1 more Smart Citation
“…It seems likely that this feature of asymmetry about both the apical and transapical axes in members of the Cymbellales has been achieved independently many times, rather than a feature that is diagnostic for a natural group of taxa. Recently many novel taxa representing multiple lineages of diatoms were described from Asia, in particular, tropical Asia (Glushchenko et al 2019a, b;Thacker et al 2019;Liu et al 2019;Roy et al 2019;Kulikovskiy et al 2020). These discoveries confirm that Asia is the hotspot of diatom diversification as proposed by Kociolek (2019) and the same finding need to be strengthened using molecular phylogenetic tools.…”
Section: Discussionmentioning
confidence: 79%
“…Southeast Asia is a floristically interesting region, from which many new genera and species of centric and pennate diatoms have been described recently (see Gusev and Kulikovskiy 2014;Glushchenko et al 2016Glushchenko et al , 2017Glushchenko et al , 2018Glushchenko et al , 2019Kapustin et al 2017Kapustin et al , 2019Liu et al 2018;Kulikovskiy et al 2019Kulikovskiy et al , 2020Rybak et al 2019). Several Adlafia species have been recorded previously from Southeast Asia.…”
Section: Introductionmentioning
confidence: 99%